Representation of Piety in Subuh Prayer Memes on The Internet: A Meanings and Media Perspective - Sunaryanto; Rizal, Sofyan; Syamsuri, Ahmad Rofi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
This research aims to critically analyze the representation of the meaning of piety in Subuh prayer memes on the internet. This research is important to carry out because many memes have been found with Islamic themes or Islamic da’wah, which carry various meanings of gender ideology, conservatism, religion, religious liberalism, and other related concepts. The theoretical framework employed in this research is meanings and media, which comprises four distinct concepts: semiotics, structuralism, denotation and connotation, and code (including myth and ideology). This study uses a qualitative content analysis method with semiotic analysis as the primary approach. The data were collected through purposive sampling, focusing on four (4) memes with the theme of Subuh prayers and their relation to social phenomena, namely New Year celebrations, watching football, the lunar eclipse and the soap opera Eclipse, as well as Eid al-Fitr celebrations. This research found that Subuh prayer memes on the internet use various texts which signify the ideological struggle of conservative Islamic groups. Popular culture and local culture for conservative Islamic groups must be rejected because it is the reason why Muslims do not perform the Subuh prayer in congregation at the mosque. The meanings of denotation, connotation, and structuralism are the aspirations to construct a structure based on unadulterated Islamic tenets that are not mixed with popular culture or local culture. In code, Subuh prayer memes on the internet represent the mythical and ideological struggle of conservative Islamic groups who want to build a society based on pure Islamic teachings.